2020
DOI: 10.37268/mjphm/vol.20/no.2/art.422
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Clinical Features and Laboratory Profile of Dengue Fever in Outpatient Setting

Abstract: Dengue fever (DF) is one of the common mosquito-borne viral diseases. It is transmitted by Aedes aegypti and Aedes albopictus.The aim to study the clinical and laboratory manifestations of serologically confirmed cases of DF in outpatient clinics.This cross-sectional study was carried out in outpatient setting. According to WHO criteria all patients above 14 years old who were suspected to have DF were tested by IgM dengue antibody test. Additionally all patients underwent history, clinical examination and inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
3
4
1
Order By: Relevance
“…Fever (96.5%) was the most common clinical symptom in this study and was the common finding in other studies too (7,9,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The second most common symptom was headache (40.6%) which was similar to the findings of other studies (7,13).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Fever (96.5%) was the most common clinical symptom in this study and was the common finding in other studies too (7,9,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The second most common symptom was headache (40.6%) which was similar to the findings of other studies (7,13).…”
Section: Discussionsupporting
confidence: 90%
“…With similar cut-off values also, the difference may be likely due to the timing of blood analysis also. Some may have been in febrile phase whereas others may have been in critical phase (12, 13, 18, 19, 22).…”
Section: Discussionmentioning
confidence: 99%
“…This study also replicate this statement. Other study also had the similar findings 11,12 . This study also showed that decreasing platelet count is associated with the severe dengue.…”
Section: Discussionsupporting
confidence: 75%
“…On the other hand, prevalence of retro orbital pain was much lower than other studies (46% vs. 78%) 12 . Previous history of dengue is found to be the predictor of severity.…”
Section: Discussioncontrasting
confidence: 72%
“…One study on the dengue fever prevalence assessed that 38 million people in 127 states are at jeopardy of contracting virus of dengue. According to several recent studies, around 3.6 billion people are at risk of getting dengue infections, with around 230 million new infections each year, including over two million cases of serious disease (DHF / DSS) and 21,000 expiries [9][10] . Dengue infection should be treated as a solitary ailment with various clinical pictures, vacillating from symptomless situations to severe clinical sequences, which may result in high mortality and morbidity.…”
Section: Introductionmentioning
confidence: 99%